Une ferme de l'Armorique gauloise Le Boisanne à Plouër-sur-Rance (Côtes-d'Armor) - Menez, Yves (Documents d'archéologie française, 1996)
Discovered during the construction of a four- lane trunk road (N 176) near Dinan, the Iron Age farm at Le Boisanne is but a modest rural settlement ; it constituted however an ideal subject of study. One can follow without interruption its evolution during a very long period, from the 4th century BC up to the 3rd century AD. The stratigraphy, the structures and the artefacts are presented in detail. The farm is placed in its context, both geographical (the Rance estuary) and historic (Armorican Iron Age). This study is concluded by a broad reflection, extending outside the purely regional framework: on the function and evolution of "native farms" or aedificia (archaeological myth or reality ?) of the Iron Age and gallo-roman periods.